The Ready System of Clean Water for Population in Musuk District to Respon Dry Season - Yuli Priyana; Dina Safriningsih (Forum Geografi, 2005)
This research about ready system of clean water in District of Musuk, Sub-Province of Boyolali. This research aim to study how ready system of clean water, research area especially of dry season. That wish to know how much amount of resident drinking water consumption at area District of Musuk. The method of research in this research is survey method. The data which collected in this research consist of primary data result of interview by 150 responded (head of house hold) and perception in field. Secondary data an obtain from governmental institution, books, other resource person and reference related to this topic of research. Intake of sample done with area of random sampling, to know the target of research to description analyses and tabulation. The result of research indicate that ready system of clean water at dry season most relying on rainwater with accommodating the rainwater at pools, besides to overcome water of water supply of rain of society buy water of springs pass tank truck, small to partly use surface water and also of PDAM. Water consumption at mean dry season 48.47 liter/day/capita. But at high area (volcanic slope) its slimmer consumption in comparing plain area of Fluvial foot/feet of Volcano.